Efektifitas Penerapan Metode Talaqqi dalam Pendampingan Penghafal Al-Qur’an - Awaliah Nur Hikmah, Octa; Musyaddad, Anwar; Astuti, Dwi (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
The Al-Qur’an Memorizing Assistance Program using the Talaqqi method is an effort to make it easier for children to memorize kalamullah in accordance with the rules of the science of tajwid, because the system is face to face and the children face the teacher one by one making it easy for the teacher to identify every mistake in a child's reading of the Koran. The focus of the objective of this service research is the effectiveness of applying the Talaqqi method in assisting memorizing the Al-Qur’an by Stai Ibnu Rushd KKN students at An-Najiyah TPA. The method used is the Participatory Action Research method or what is usually called PAR, which is research used by the author where the author directly participates as a companion at the service location, namely at TPA An-Najiyah Dusun 2, Sindang Agung Village. As a result, by implementing the talaqqi method in assisting children to memorize the Qur'an, children become more enthusiastic in memorizing, children's pronunciation which was originally still carried by regional languages is decreasing, children's awareness of paying attention to the laws of recitation when memorization gets higher.